ROE and financial structure of mining companies period 2004-2013 - Pacheco Mexzon, Raimundo Renaun (2019)
The research work called “ROE and FINANCIAL STRUCTURE OF MINING COMPANIES PERIOD 2004-2013” was developed after considering the following questions:What has been the return on equity performance (ROE: Return on Equity) of the Peruvian mining sector companies that are listed on the Lima Stock Exchange during the 2004-2013 period?Which companies in this sector of the Peruvian economy that are listed on the Lima Stock Exchange have optimized their financial structure?To answer them, five chapters were developed and it was concluded that not all companies present the same profitability opportunities (ROE) and this differs according to the size of the company and the behavior of its financial structure.